MEDIA AND PUBLIC TRUST TOWARDS COVID-19 INFORMATION - Muhammad Yunus Patawari (Fakultas Seni Rupa dan Desain ITB, 2021)
Mass media is one of the leading sectors in handling COVID-19. Amidst current health emergency, public trusttowards the information conveyed by the mass media is the key to successful mitigation. Various types of newsregarding massive COVID-19 reports in several media channels have the potential to cause information bias whichends in pros and cons. Insubstantial debates in varied media are counter-productive to the efforts of various partiesin educating the society to avoid misinformation. Based on this, it is important to know the media that are referencesand that gain public trust in seeking information. This study examines the level of public trust in information aboutCOVID-19 in the mass media, both old and new media, using an online questionnaire methodology on May 3, 2020,which was given to 60 respondents. The results show that the respondents’ level of faith in television is higher, but itsconsumption by viewers is much lower than that of online media (news sites and social media). The results showedthat viewers still deemed television a reliable reference for information. From these data it was found out why themedia are rarely used by the people but are able to gain high trust in the eyes of the public. The results of this studyare expected to provide an overview of the attitudes and behavior of the community in understanding COVID-19information so that relevant parties can make appropriate policies in the perspectives of media and communication.